2012
DOI: 10.3109/09553002.2012.715790
|View full text |Cite
|
Sign up to set email alerts
|

Influence of whole-body vibration on biodistribution of the radiopharmaceutical [99mTc]methylene diphosphonate in Wistar rats

Abstract: The analysis of the results indicates that the vibration could produce metabolic alterations with influence in the uptake of the radiopharmaceutical 99mTc-MDP in bone, stomach, bowel, prostate, kidney and bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Previously, Pereira et al [22] have shown that, in rats, the exposure to vibration with 20 Hz can alter the uptake of a radiopharmaceutical in some organs. Frederico et al [16] reported that the association between coriander and WBV (12 Hz) increases the uptake of Na 99m TcO 4 in spleen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, Pereira et al [22] have shown that, in rats, the exposure to vibration with 20 Hz can alter the uptake of a radiopharmaceutical in some organs. Frederico et al [16] reported that the association between coriander and WBV (12 Hz) increases the uptake of Na 99m TcO 4 in spleen.…”
Section: Discussionmentioning
confidence: 99%
“…The biological effects of the WBV exercises in an organ seem to be also dependent on the frequency [16,22]. Miyazaki, 2000 has evaluated the electrogastrography (EGG) in healthy male volunteers’ exposure to vibrations of 4, 8, and 16 Hz.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase could possibly be due to the caffeine, a component of guarana [4]. According to Behrens et al [38], the ingestion of caffeine induced increases in the voluntary activation and strength of the quadriceps muscle during isometric, concentric, and eccentric contractions. Furthermore, in general, the interventions did not promote modifications at different levels (molecular or cellular) in the several organs that were capable of interfering in the uptake of the radiopharmaceutical Na 99m TcO 4 .…”
Section: Discussionmentioning
confidence: 99%